The Effectiveness of 3D Sipaurangi Learning Media in Increasing Students' Self-efficacy - Nurzakinah, Salsabilla; Muhajir, Muhajir; Arifin, Jamaluddin (JED (Jurnal Etika Demokrasi), 2025)
This study aimed to measure the effectiveness of using Sipaurangi 3D learning media in enhancing students' self-efficacy in the subject of Pancasila Education. The Sipaurangi 3D media was developed using the ADDIE model, which includes the stages of analysis, design, development, implementation, and evaluation, to ensure that the product meets learning needs. This media was designed to integrate interactive elements that are concrete and engaging, thereby providing students with a more immersive learning experience and motivating them to become more active in the learning process. The study was conducted in Grade IV at SDI Gunung Sari Baru, Makassar City, using data collection methods such as questionnaires, observations, and learning achievement tests. The results showed that Sipaurangi 3D media significantly enhanced students' self-efficacy, as evidenced by an increase in self-efficacy questionnaire scores before and after using the media, with a significance value of (p 0.05). In addition, students gave positive responses to this media, as demonstrated by their increased confidence and motivation in understanding the Pancasila Education material. Teachers also provided positive feedback, stating that this media is practical and effective in capturing students' attention and increasing their participation during the learning process. Thus, Sipaurangi 3D learning media can be proposed as an innovative alternative to improve the quality of learning and student engagement in the teaching-learning process, particularly in subjects that focus on character building and the reinforcement of national values.